THE EFFECT OF CHARACTER EDUCATION ON STUDENT ACADEMIC ACHIEVEMENT: A LITERATURE REVIEW - Hayyatun Mawaddah; Cynthia Petra Haumahu; Criezta Korlefura (Indonesian Journal of Education (INJOE), 2025)
This study aims to review the literature that discusses the effect of character education on students' academic achievement in the school environment. The results of the review show that character education has a significant positive impact on improving academic achievement. A planned and consistent character education programme can help students develop ethical and moral values, such as discipline, responsibility and hard work, which contribute to better academic performance. In addition, the social and emotional skills acquired also support positive interpersonal relationships in the school environment. However, the effectiveness of character education programmes may vary depending on the implementation method, school context and student characteristics. Therefore, continuous evaluation and improvement are needed to ensure all students can gain maximum benefits. This research underlines the importance of character education in shaping students' academic excellence and virtuous character.